Subsea manifold installation: Operational windows estimation based on hydrodynamic model testing. (1st January 2021) - Pestana, Rafael Guimarães; Fonseca de Carvalho e Silva, Daniel; Gomes, Camila do Nascimento; de Oliveira Carvalho, Leonardo; Vileti, Vinicius; de Tarso Themistocles Esperança, Paulo; Kim, Moohyun
Abstract: In this paper, added mass and drag coefficients for typical subsea manifolds installation conditions are determined through experimental model tests. The forced oscillation test results show that the equipment has large drag coefficients in the low Keulegan-Carpenter (KC) region, which leads to higher damping. The results also show that the added mass increases with higher KC number values and is appreciably larger than those found in the literature for flat plates, even when extrapolated to a prism. With the experimentally obtained hydrodynamic coefficients, a series of analytical and numerical simulations are conducted for a typical installation operation for various sea states. The results show that the operational windows for subsea equipment installation are expanded when compared to the current conventional approach. Highlights: Forced-oscillation model tests are carried out to assess Morison hydrodynamic inertia and drag force coefficients for large subsea manifolds used in oil and gas production facilities. Tests covered a range of KC (Keulegan-Carpenter number) that reflect real typical operational conditions. Test results show larger values for inertia and drag coefficients than those typically adopted in the industry. Larger inertia coefficients are found for larger KC and larger drag coefficients for lower KC. Analytical and numerical models based on test results showed expanded safe operational conditions and potential cost reduction.